Influence of the extracellular matrix on the frictional properties of tissue-engineered cartilage. (20th July 2007) - Plainfossé, M.; Hatton, P.V.; Crawford, A.; Jin, Z.M.; Fisher, J.
Abstract : Low-friction surfaces are critical for efficient joint articulation. The tribological properties of articular cartilage have been studied extensively in native tissue and joints. Despite their importance, very few studies have examined the frictional properties of tissue-engineered cartilage. We have therefore reviewed the relationship between composition, structure and friction in tissue-engineered cartilage.